The Effect of Different Degrees of Regional Accentedness in Radio Commercials: An Experiment with German Consumers. Issue 4 (8th August 2019) - Hendriks, Berna; van Meurs, Frank; Behnke, Gwendolyn
Abstract: The present study investigated the use of a regional accent with varying strengths in product and service commercials. In a 2 (type of commercial: product/service) × 3 (accent: strong German regional / moderate German regional / standard German) between-subject design, 218 German native speakers evaluated product and service commercials. Findings suggest that the effects of regional accents were limited. In the product commercial, the speaker with a moderate accent was attributed more warmth than a speaker with a standard accent. In the service commercial, the attitude towards the service was more negative for the moderate than for the standard accent.